A comparative study of the effect of Benson's relaxation technique and Zekr (rosary) on the anxiety level of patients awaiting abdominal surgery - A.R Nikbakht Nasrabadi; T Taghavi Larijani; M Mahmoudi; F Taghlili (Tehran University of Medical Sciences, 2005)
Introduction: Surgery is a stressful event and patients undergoing surgery experience anxiety. Any effort to reduce anxiety of surgical patients should be of priority in nursing care of preoperative patients. The purpose of this study was to compare the effect of Benson relaxation technique and Zekr (rosary) on anxiety level of patients awaiting abdominal surgery. Materials and Methods: This research is a quasi-experimental study carried out on patients who were admitted for abdominal surgery in a affiliated hospital to Tehran University of Medical Sciences in the year 2004. A total of 70 patients were chosen and divided randomly into two groups. We used Benson's relaxation technique in first and Zekr in the second group. The patients were assessed on the day before surgery and on the day of surgery by a questionnaire that included demographic information and Spielberger anxiety tool. Vital signs were also recorded. The data were analyzed by SPSS computer software. The differences between pre and post intervention values were analyzed using paired t test, and between groups using independent t test and 2. Results: Although there was a significant difference between mean anxiety level before and after intervention in both Zekr (p<0.006) and relaxation group (p0.05). There was also a significant reduction in systolic blood pressure and pulse rate in both groups (p<0.05). Conclusion: It seems that Zekr is as effective as Benson's relaxation technique in reducing anxiety level of patients and both can be used to reduce anxiety level of patients awaiting abdominal surgery.